A review of gallium nitride LEDs for multi-gigabit-per-second visible light data communications - Rajbhandari, Sujan; McKendry, Jonathan J D; Herrnsdorf, Johannes; Chun, Hyunchae; Faulkner, Grahame; Haas, Harald; Watson, Ian M; O'Brien, Dominic; Dawson, Martin D (Semiconductor science and technology, 2017)
The field of visible light communications (VLC) has gained significant interest over the last decade, in both fibre and free-space embodiments. In fibre systems, the availability of low cost polymer optical fibre (POF) that is compatible with visible data communications has been a key enabler. In free-space applications, the availability of hundreds of THz of the unregulated spectrum makes VLC attractive for wireless communications. This paper provides an overview of the recent developments in VLC systems based on gallium nitride (GaN) light-emitting diodes (LEDs), covering aspects from sources to systems. The state-of-the-art technology enabling bandwidth of GaN LEDs in the range of >400 MHz is explored. Furthermore, advances in key technologies, including advanced modulation, equalisation, and multiplexing that have enabled free-space VLC data rates beyond 10 Gb s−1 are also outlined.